Instructional materials in communication arts (English) for first year and second year unit I geared to the value-work-oriented curriculum - Mata, Pilar Comaya 1940- (Quezon City University of the Philippines Diliman, 1974)
Instructional materials are prepared in this study using "English" as the medium. The language skills are taught by combining instruction with the different content areas in the first and second year high school levels. These materials are done in response to the need for instructional materials geared towards a value-work-oriented curriculum which is the primordial concern in the New Society.
Thesis (M.A.T. English as a second language)--University of the Philippines.
Keywords: English language -- Study and teaching; Teaching -- Aids and devices